Archaeology and ethnography along the Loango Coast in the south west of the Republic of Congo - Wait, G. A. (Archaeopress archaeology, 2018)
In 2011 and 2012, Dr Gerry Wait and Dr Ibrahima Thiaw undertook an Environmental and Social Impact Assessment (ESIA) project in Kouilou Department in the southwest region of the Republic of the Congo. The initiative had been commissioned by SRK Consulting UK for Elemental Minerals Ltd relating to a proposed potash mine. These landscapes were little known in terms of the sites and monuments from the distant and more recent past. That the area was important in the understanding of migrations along the African coast had been demonstrated in a pioneering set of excavations by Denbow. This base line study was undertaken to identify and evaluate cultural resources which might need further investigation